Incident data in enhancing school safety: an example from Finland - Lindfors Eila (INDERSCIENCE PUBLISHERS, 2025)
Safety and security is a multi-faced phenomenon that is an essential part of students’ and staff’s well-being at school, which is well documented as the main issue in a good learning environment. However, very little is known about incidents that happen at schools, but a catalogue of these incidents could serve as a learning tool for proactive management of the safety culture.
Incidents occur in relation to physical, social, psychological and pedagogical factors. To develop a safety culture, there is need to record, monitor and analyse incidents (near-misses, accidents and injuries). There are no systematic procedures in regular use that would allow schools as organisations to learn
from incidents and implement alterations to develop their safety culture. In the study of 168 incidents from three comprehensive schools in Finland, data were collected and monitored in a digital system. The incidents were categorised into physical, social, psychological and pedagogical categories. This paper gives
prior knowledge of incidents in pedagogical category regarding what happened, where and to whom.